Global research trends on case managers in chronic disease management: a bibliometric analysis (2005–2025) - Asfarada, Muhammad Rizky; Mediawati, Ati Surya; Komariah, Maria; Firdaus, Mohd Khairul Zul Hasymi; Maulana, Sidik; Musmulyono, Musmulyono (Elsevier, 2026)
Background: Chronic diseases are the leading global cause of mortality, and fragmented care can worsen outcomes, especially in health systems with workforce and coordination constraints. Case management-related roles (case managers, care coordinators, patient navigators) are increasingly used to support continuous, integrated, people-centered care. However, prior reviews mainly assess effectiveness in specific diseases or settings and rarely map global publication trends, geographic disparities, collaboration patterns, or thematic evolution. Aim: To map the global research landscape on case management-related roles in chronic disease management (2005–2025), including publication trends, geographic contributions, influential documents, and thematic structures. Methods: A bibliometric analysis was conducted using Scopus and PubMed. English-language articles, reviews, and conference papers (2005–2025) were included. Records were deduplicated and analyzed in VOSviewer using keyword and title/abstract term co-occurrence mapping; screening followed PRISMA 2020. Results: After screening, 574 publications were included. Output increased markedly after the mid-2010 s and was concentrated in high-income countries, with limited representation from low- and middle-income countries. Co-occurrence mapping showed interconnected themes spanning integrated care models, community/navigation approaches, role development, and evaluation/implementation, with recent emphasis on multimorbidity, self- management, and technology-enabled coordination. Conclusion: Research on case management-related roles in chronic disease care has expanded and diversified toward integrated, people-centered, longitudinal care. Future work should strengthen implementation-focused evidence (including outcomes and costs), reduce geographic inequities, and clarify how digital tools are embedded within redesigned care pathways to support scalable and equitable chronic care.